(untitled) (Economics and region, 2022)
The article examines the current state and potential opportunities of land resources. It was found that Ukraine has a powerful land potential and a favorable geographical location. The peculiarities of the use of land resources, the state and efficiency of the use of agricultural land by landowners and land users are analyzed. Irrational use of land resources by landowners and oversaturation of arable land with agricultural crops have been established. The improvement of the management mechanism in the field of land use and protection was studied. The experience of Germany in land use and the Law on Land: how the market works in France and whether Ukraine should take over are considered. The natural and geographical location of Ukraine in the center of Europe, combined with the industriousness of its population, makes it possible to grow almost all agricultural crops (cereals, sugar beets, potatoes, vegetables, fruits and berries, fodder crops, etc.) and produce all types of livestock products (milk, m meat of all kinds, eggs, fish, honey, etc.). The volume of production of agricultural products grows year by year and exceeds the needs of national food security, which makes it possible to increase the export potential and contribute to the solution of the world crisis of providing the population with food products. Ukraine, which has a powerful land potential and is assigned the role of a strategic world food producer. There is a need to substantiate the reserves of capacity building in terms of expanding the area of agricultural massifs and intensifying their use. The purpose of the study is to analyze the current state and potential opportunities of Ukraine’s land resources in addressing food security. The main tasks of building the land potential in Ukraine in the context of solving food security are currently: implementation of the principles of strategic management in the field of use and protection of land resources that are in private and state ownership, and this also applies to leased land massifs; ensuring rational use of land, in particular taking into account long-term regional programs and plans for the development of territorial communities, increasing the level of transparency and publicity during the formation and implementation of state land policy and the level of awareness of the population, landowners and land users regarding the problems of land degradation and sustainable land use; prevention of soil degradation processes, increasing the level of soil fertility; reclamation of disturbed lands.